Aging and the Indian Diaspora : Cosmopolitan Families in India and Abroad. - Lamb, Sarah E. (Tracking Globalization.)
The proliferation of old age homes and increasing numbers of elderly living alone are startling new phenomena in India. These trends are related to extensive overseas migration and the transnational dispersal of families. In this moving and insightful account, Sarah Lamb shows that older persons are innovative agents in the processes of social-cultural change. Lamb's study probes debates and cultural assumptions in both India and the United States regarding how best to age; the proper social-moral relationship among individuals, genders, families, the market, and the state; and ways of finding meaning in the human life course.